O Cerimonial e o protocolo nos eventos dos dez anos do campus IV UFPB - Barros, Elijarlyson José da Silva (2017)
Currently, there are several scenarios that the Executive Secretariat acts, not being different for the area of communication in the case of the University Public Ceremonial. In this investigation are analyzed the protocol procedures used in the events commemorating the ten years of Campus IV – UFPB, starting from the rules established by the public ceremonial. Are the specific objectives: observe if the composition of the Bureau, the execution of the Brazilian national anthem and the order of statements have been made in accordance with the Federal Decree 70,274; check the order of precedence between the flags, from the criteria established by Decree 70,274/1972; analyze, from the ceremonial team vision, how the content studied in the discipline of ceremonial, Protocol and Business Etiquette contributed the work played in events in celebration of 10 years of Campus IV and analyze the formation of professional secretariat in conducting the ceremony. As theoretical basis was used the research of Velloso (1999), Lukower (2010), Lukower (2015), Luz (2005), Viana (1998) among others to come help search, bringing information on the University and Public Ceremonial specifics of public ceremonies, was used also use as support, the Federal Decree 70,274/72. The study used a qualitative approach, deductive, descriptive type method and applied in nature. Thus, a semi-structured interview with a teacher, two professionals of Secretariat and two pupils of the course of Executive Secretariat of UFPB. It is concluded from the information obtained that the rules indicated by Decree 70.274 / 72 were not applied in accordance with the rules of the public ceremonial. In addition, it was noticed that the knowledge acquired in the Ceremonial, Protocol and Business Label discipline helped the interviewees to perform the events analyzed, identifying the knowledge about the general rules of the public ceremonial, emphasizing the practice of these activities by the professional of Secretariat at UFPB.